Fluctuating locked-in syndrome as a presentation of a bilateral pontine infarction. Issue 5 (October 2016) - García-Esperón, Carlos; López-Cancio, Elena; Martín-Aguilar, Lorena; Millán, Mónica; Castaño, Carlos; Munuera, Josep; Dávalos, Antoni
The "pontine warning syndrome" is characterized by recurrent episodes of motor hemiparesis, dysarthria and horizontal gaze palsy associated with basilar artery branch infarction. We report a case of a patient who presented with recurrent, self-limited episodes of locked-in syndrome, related to a bilateral pontine infarction. As far as we know, this clinical presentation as a subtype of pontine warning syndrome has never been described. We discuss the case, the differential diagnosis of the neuroimaging and the possible underlying mechanism.